EXPLORING THE RELATIONSHIP BETWEEN PROFESSIONAL DEVELOPMENT PROGRAMS AND TEACHER PERFORMANCE IN KENDRIYA VIDYALAYAS - Gaurav Saraswat; Meena Sirola (IJRDO - Journal of Business Management, 2025)
This study investigates the impact of professional development programs on teachers' performance in Kendriya Vidyalayas. This paper examines the roles of participation in programs, relevance to teaching needs, delivery methods, and teacher engagement. A quantitative research approach was adopted for the study, with data collected from 384 teachers through a standardized questionnaire. The findings reveal that active participation in professional development programs significantly improves teacher performance (β = 0.676, P < 0.05). What is more, the relevance of programmes to specific needs for teaching was found to influence teacher performance positively, β = 0.676, P < 0.05. A further finding of the study is that delivery methods of the programme had a high impact on teacher performance β = 0.742, P < 0.05. Moreover, teacher engagement was a mediator that links professional development program characteristics with teacher performance. Teacher engagement indirectly affected teacher performance to a great extent (0.409, P < 0.001). SEM was utilized to study these relationships and establish that teacher engagement is necessary for improving professional development programs' impact on teacher performance. This leads to the importance of professional development programs being meaningful, relevant, and delivered in ways that make teachers actively engage in them. This result underlines the importance of well-designed and thoughtfully delivered professional development initiatives in improving teacher performance, particularly in the Kendriya Vidyalayas context.